A new scoring system for the chances of identifying a BRCA1/2 mutation outperforms existing models including BRCAPRO. Issue 6 (1st June 2004) - Evans, D G R; Eccles, D M; Rahman, N; Young, K; Bulman, M; Amir, E; Shenton, A; Howell, A; Lalloo, F
Abstract : Purpose: To develop a simple scoring system for the likelihood of identifying a BRCA1 or BRCA2 mutation. Methods: DNA samples from affected subjects from 422 non-Jewish families with a history of breast and/or ovarian cancer were screened for BRCA1 mutations and a subset of 318 was screened for BRCA2 by whole gene screening techniques. Using a combination of results from screening and the family history of mutation negative and positive kindreds, a simple scoring system (Manchester scoring system) was devised to predict pathogenic mutations and particularly to discriminate at the 10% likelihood level. A second separate dataset of 192 samples was subsequently used to test the model's predictive value. This was further validated on a third set of 258 samples and compared against existing models. Results: The scoring system includes a cut-off at 10 points for each gene. This equates to >10% probability of a pathogenic mutation in BRCA1 and BRCA2 individually. The Manchester scoring system had the best trade-off between sensitivity and specificity at 10% prediction for the presence of mutations as shown by its highest C-statistic and was far superior to BRCAPRO. Conclusion: The scoring system is useful in identifying mutations particularly in BRCA2 . The algorithm may need modifying to include pathological data when calculating whether to screen for BRCA1 mutations. It is considerably less time-consuming for clinicians than using computer models and if implemented routinely in clinical practice will aid in selecting families most suitable for DNA sampling for diagnostic testing.